Dually fibronectin/CD44-mediated nanoparticles targeted disrupt the Golgi apparatus and inhibit the hedgehog signaling in activated hepatic stellate cells to alleviate liver fibrosis - Li, Yanping; Zhang, Ting; Zhang, Jinhang; Liu, Qinhui; Jia, Qingyi; Chen, Wenfei; Tang, Qin; Xiong, Yimin; Xia, Yan; Xu, Ying; Mo, Li; Huang, Yuan; et al. (Biomaterials, 2023)
Liver fibrosis is featured by activation of hepatic stellate cells (HSCs) and excessive accumulation of extracellular matrix (ECM). The Golgi apparatus in HSCs plays a vital role in synthesis and secretion of ECM proteins, while its targeted disruption in activated HSCs could be considered as a promising approach for liver fibrosis treatment. Here, we developed a multitask nanoparticle CREKA–CS–RA (CCR) to specifically target the Golgi apparatus of activated HSCs, based on CREKA (a specific ligand of fibronectin) and chondroitin sulfate (CS, a major ligand of CD44), in which retinoic acid (a Golgi apparatus-disturbing agent) chemically conjugated and vismodegib (a hedgehog inhibitor) encapsulated. Our results showed that CCR nanoparticles specifically targeted activated HSCs and preferentially accumulated in the Golgi apparatus. Systemic administration of CCR nanoparticles exhibited significantly accumulation in CCl4-induced fibrotic liver, which was attributed to specific recognition with fibronectin and CD44 on activated HSCs. CCR nanoparticles loaded with vismodegib not only disrupted Golgi apparatus structure and function but also inhibited the hedgehog signaling pathway, thus markedly suppressing HSC activation and ECM secretion in vitro and in vivo. Moreover, vismodegib-loaded CCR nanoparticles effectively inhibited the fibrogenic phenotype in CCl4-induced liver fibrosis mice without causing obvious toxicity. Collectively, these findings indicate that this multifunctional nanoparticle system can effectively deliver therapeutic agents to the Golgi apparatus of activated HSCs, thus has potential treatment of liver fibrosis with minimal side effects.